Pakistan's Diplomatic Maneuvering: Facilitating Sino-American Rapprochement in 1971-72 - A Historical Approach - Ismail, Aneta; Arif, Muhammad; Yong, Wang; Weihong, Wang (Journal of Legal and Cultural Analytics, 2024)
This paper examines the vital role, which Pakistan played in bringing about the Sino- American normalization in 1971-72. The study shall add to Cold War diplomacy by uncovering Pakistan’s strategic location that facilitated top secret negotiations that escalated to Dr. Henry Kissinger’s visit to Beijing followed by President Nixon. As such, this research, based on the analysis of declassified documentation, memoirs, and oral histories analyzes the change in perceptual categorization of Pakistan from a minor to a gross strategic actor. This concern focuses the historical research for the period of 1971-72 and it uses historiographical sources. Findings indicate that Pakistan’s role in geopolitics specifically highlights the significance of the role of small states in major diplomatic shifts during the Cold War.